2019
DOI: 10.2139/ssrn.3346371
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Pressures and Sectoral Inflation Dynamics

Abstract: In a production network, shocks originating in individual sectors do not remain confined to individual sectors but permeate through the pricing chain. The notion of "pipeline pressures" alludes to this cascade effect. In this paper we provide a structural definition of pipeline pressures to inflation and use Bayesian techniques to infer their presence from quarterly U.S. data. We document two insights. (i) Due to price stickiness along the supply chain, we show that pipeline pressures take time to materialize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 82 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…31 Appendix Table C.2 shows that all of the top ten firms loading on the second factor are technology companies, and the bottom ten consists of nine energy firms and a petroleum shipping company. 32 A role for price pressures in the inter-firm network is supported by Smets et al (2019), who found evidence of inflation being passed through production networks. 33 Nine of the top ten firms by their loadings on the third factor in Appendix Table C.3 are energy related, and the bottom ten with negative loadings are all financial firms.…”
Section: Common Factors In Equity Returnsmentioning
confidence: 99%
“…31 Appendix Table C.2 shows that all of the top ten firms loading on the second factor are technology companies, and the bottom ten consists of nine energy firms and a petroleum shipping company. 32 A role for price pressures in the inter-firm network is supported by Smets et al (2019), who found evidence of inflation being passed through production networks. 33 Nine of the top ten firms by their loadings on the third factor in Appendix Table C.3 are energy related, and the bottom ten with negative loadings are all financial firms.…”
Section: Common Factors In Equity Returnsmentioning
confidence: 99%
“…2 More closely related to our paper, Franzoni et al (2023) provides evidence that supplychain constraints lead to a decrease in competition, showing that these constraints can help explain about 19% of the U.S. inflation in industries with more asymmetric firm size distri-2 A related stream of literature delves into the transmission of shocks through the production network. Smets et al (2019) finds that price stickiness and sectoral shocks play a crucial role in understanding headline/disaggregated inflation. Auer et al (2019) emphasizes the importance of international input-output linkages in synchronizing PPI across countries.…”
Section: Related Literaturementioning
confidence: 99%